Oscillating droplet tribometer for sensitive and reliable wetting characterization of superhydrophobic surfaces. Issue 1 (27th July 2022) - Junaid, Muhammad; Nurmi, Heikki A.; Latikka, Mika; Vuckovac, Maja; Ras, Robin H. A.
Abstract: Accurate wetting characterization is crucial for the development of next‐generation superhydrophobic surfaces. Traditionally, wetting properties are measured with a contact angle goniometer (CAG) suitable for a broad range of surfaces. However, due to optical errors and challenges in baseline positioning, the CAG method suffers from inaccuracies on superhydrophobic surfaces. Here we present an improved version of the oscillating droplet tribometer (ODT), which can reliably assess wetting properties on superhydrophobic surfaces by measuring the frictional forces of a water‐based ferrofluid droplet oscillating in a magnetic field. We demonstrate that ODT has superior accuracy compared to CAG by measuring the wetting properties of four different superhydrophobic surfaces (commercial Glaco and Hydrobead coatings, black silicon coated with fluoropolymer, and nanostructured copper modified with lauric acid). We show that ODT can detect the small but significant changes in wetting properties caused by the thermal restructuring of surfaces that are undetectable by CAG. Even more, unlike any other wetting characterization technique, ODT features an inverse sensitivity: the more repellent the surface, the lower the error of measurement, which was demonstrated by experiments and simulations. Abstract : Wetting characterization is typically carried out with a contact angle goniometer measuring the advancing and receding contact angles. However, the contact angle goniometer does not have sufficient sensitivity for superhydrophobic surfaces. Here, we use an oscillating droplet tribometer to accurately characterize superhydrophobic surfaces, demonstrating its superior sensitivity compared to a contact angle goniometer.